Estudo da estabilidade térmica de adoçantes naturais e artificiais - Freire, Rosimere Maria Lima (2010)
Sweeteners provide a pleasant sensation of sweetness that helps the sensory quality of the human diet, can be divided into natural sweeteners such as fructose, galactose, glucose, lactose and sucrose, and articial sweeteners such as aspartame, cyclamate and saccharin. This work aimed to study the thermal stability of natural and artificial sweeteners in atmospheres of nitrogen and syntetic air using thermogravimetry (TG), derivative thermogravimetry (DTG), Differential Thermal Analysis (DTA) and Differential Scanning Calorimetry (DSC). Among the natural sweeteners analyzed showed higher thermal stability for the lactose and sucrose, which showed initial decomposition temperatures near 220 ° C, taking advantage of the lactose has a higher melting point (213 ° C) compared to sucrose (191 ° C). The lower thermal stability was observed for fructose, it has the lowest melting point (122 °C) and the lower initial decomposition temperature (170 °C). Of the artificial sweeteners studied showed higher thermal stability for sodium saccharin, which had the highest melting point (364 ° C) as well as the largest initial decomposition temperature (466 ° C under nitrogen and 435 ° C in air). The lower thermal stability was observed for aspartame, which showed lower initial decomposition temperature (158 ° C under nitrogen and 170 ° C under air). For commercial sweeteners showed higher thermal stability for the sweeteners L and C, which showed initial temperature of thermal decomposition near 220 ° C and melting points near 215 ° C. The lower thermal stability was observed for the sweetener P, which showed initial decomposition temperature at 160 ° C and melting point of 130 °C. Sweeteners B, D, E, I, J, N and O had low thermal stability, with the initial temperature of decomposition starts near 160 °C, probably due to the presence of aspartame, even if they have as the main constituent of the lactose, wich is the most stable of natural sweeteners. According to the results we could also realize that all commercial sweeteners are in its composition by at least a natural sweeteners and are always found in large proportions, and lactose is the main constituent of 60% of the total recorded